2021
DOI: 10.1177/20503121211023357
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of nintedanib in 158 patients with idiopathic pulmonary fibrosis in real-world settings: A multicenter retrospective study

Abstract: Background: The INPULSIS trials revealed that nintedanib reduced the decline in lung function in patients with idiopathic pulmonary fibrosis. We aimed to evaluate the efficacy and safety of nintedanib in Japanese idiopathic pulmonary fibrosis patients in real-world settings. Method: Medical records of idiopathic pulmonary fibrosis patients, who received treatment with nintedanib in five institutions between July 2015 and June 2017, were reviewed. Patients with % forced vital capacity ⩾50% and % predicted diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…These results confirm the findings of previous smaller studies in Japanese patients, which reported nintedanib discontinuation rates of 47–51% [ 15 , 16 ]. In one of these previous studies, the only factor significantly associated with early discontinuation of nintedanib was poor performance status at baseline [ 15 ], whereas we found that older age, male sex, lower BSA and worse lung function (severe IPF and lower percentage predicted FVC) were associated with an increased risk of treatment discontinuation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results confirm the findings of previous smaller studies in Japanese patients, which reported nintedanib discontinuation rates of 47–51% [ 15 , 16 ]. In one of these previous studies, the only factor significantly associated with early discontinuation of nintedanib was poor performance status at baseline [ 15 ], whereas we found that older age, male sex, lower BSA and worse lung function (severe IPF and lower percentage predicted FVC) were associated with an increased risk of treatment discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the current study, as well as previous real-world studies, it appears that Asian patients (including those in Japan or Korea) have higher rates of nintedanib discontinuation (47-53%) [15][16][17] than patients in the USA or Europe (11-26%) [10][11][12][13][14]. The reason for this difference is not clear, but previous data indicate that patients with a smaller BSA are at higher risk of hepatotoxicity, dose reduction or discontinuation [20,22], suggesting that the smaller physique of Asian individuals places them at higher risk of developing AEs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The present study further confirms these findings, providing real-world evidence of nintedanib effectiveness in a population of considerable size and with a long observation period and data collection, which allowed us to evaluate the sustained effectiveness of the drug in the reduction of FVC decline rate. On this regard, our results are in line with other previous reports coming from real-life observational studies [ 5 , 24 ]; notably, the mean decline rate of FVC after the first year of treatment was also similar to those reported in open-label extension studies of the INPULSIS and TOMORROW trials [ 28 , 29 , 30 ], further underlining the effectiveness of this drug in the long-term management of IPF patients. Moreover, standing that our IPF subgroup could be considered more “fragile” than RCT populations (in terms of age, comorbidities and respiratory functional impairment), our findings are surely interesting since they support the efficacy of nintedanib in reducing disease progression also in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…From a clinical point of view, the phase 2 double-blind, dose finding, placebo-controlled TOMORROW trial (ClinicalTrials.gov identifier: NCT00514683) and the following phase 3 trials, INPULSIS-1 and -2 (NCT01335464) demonstrated the efficacy of nintedanib in reducing disease progression, leading to the approval of the drug for clinical use in idiopathic pulmonary fibrosis (IPF) [ 3 , 4 ]. The subsequent open-label extension trials and large observational real-world studies substantially confirmed the effectiveness of nintedanib in reducing disease progression rate and the risk of acute exacerbation incidence in IPF patients [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 90%